Modelling and simulation of a novel bioinspired flapping-wing rotary MAV - Huang, Xun; Lu, Linghai; Whidborne, James F.; Guo, Shijun (German Society for Aeronautics and Astronautics (DGLR: Deutsche Gesellschaft für Luft- und Raumfahrt), 2023)
Achieving high lift efficiency represents a major research focus in the Micro Air Vehicle (MAV) domain due to stringent size and payload constraints. The Cranfield research team presents a novel semi-biomimetic design called the Flapping Wing Rotor (FWR) to address this challenge. This innovative concept combines a bioinspired flapping wing mechanism with passive rotor rotation, leveraging unsteady aerodynamic principles analogous to insect flight. The research aims to highlight a promising biomimetic flapping-rotor MAV enabled through advanced modeling to unlock the benefits of bio-inspired unsteady aerodynamics. To demonstrate this approach, a 60g proof-of-concept prototype was developed alongside a digital twin methodology for modeling, simulation, and control. A mathematical model has been formulated to analyze FWR's lift generation performance and enable flight control system design for stabilization and controllability. This work concentrates on enhancing the physical modeling process. The model is refined by tuning two key aerodynamic coefficients to account for nonlinearities from unsteady aerodynamics, flexible structures, and low Reynolds number flow inherent in MAV flight. This improved model achieves superior lift prediction accuracy versus real flight test data. Ongoing efforts focus on optimizing control torque, load distribution, and stability to further augment FWR's flight capabilities.
© The Authors